(untitled) (Indian Journal of Public Health Research & Development, 2020)
Accurate diagnosis and treatment of oral diseases is an essential component of a comprehensive oral care practice. Accurate diagnosis also helps formulate the appropriate treatment plan and helps to avoid further complications from inadequate treatment and to avoid adverse effects from treatment that is not necessary for the particular patient. Obtaining an oral biopsy allows the clinician to diagnose many precancerous conditions and ensure early treatment. Biopsy may be the gold standard for final tissue diagnosis but any invasive procedure comes with its own risks and side effects. When a clinician is faced with a patient with signs and symptoms that are suggestive, but not diagnostic of a disease, he/she has the responsibility to decide between the option to treat empirically or not to treat or to perform further diagnostic tests. This paper aims to review the basic indications and contraindications of performing an oral tissue biopsy and to identify different oral mucosal lesions that may benefit from empirical therapy better than a biopsy in the early stages. Knowledge of these lesions will help the clinician avoid the undesirable outcomes that may be associated with an oral biopsy